ADMINISTRASI NEGARA KONTEMPORER UNTUK INOVASI PELAYANAN PUBLIK - Slamet Rosyadi (Master of Public Administration, Universitas Slamet Riyadi, 2017)
The environment public administration provides the situation is unpredictableand uncertain. Therefore, public administration needs to be supported byadequate capability in order to organize public services that are moreinnovative. The scarcity of budget and demands of an increasingly diversepublic administration encourages countries to do public service innovation. Tofacilitate the innovation of public service required three capabilities: thinkingahead, thinking again and thinking across. The third of these capabilities needto be supported with organizational climate that supports innovation process,namely the availability of resources, the new leadership styles, spaceslearning and incentives.Key Words: Public administration, inovation, capability, public service